Collage Games Increase the Duration of Concentration in Children with Intellectual Developmental Disorder - Riska Ardiani, Marcella; Suparmi , Suparmi; Sumijati, Sri (Kuras Institute, 2024)
Concentration is an important ability for children, especially the skill to focus attention on specific objects. Field observations show that children with intellectual developmental disorders often experience difficulties maintaining concentration during learning activities. This research aims to determine the effect of collage games on increasing learning concentration in children with intellectual developmental disorders. The hypothesis states that collage games can improve concentration duration before and after the intervention. The study used a single-subject experimental method with an A-B-A design. Baseline 1 (A-1) consisted of four 15-minute sessions in which the child-colored pictures of balls. The intervention phase (B) involved eight 15-minute sessions using collage games. Baseline 2 (A-2) was then conducted through four 15-minute coloring sessions. The instrument used was direct observation with event recording, measuring pre-test and post-test concentration duration and frequency. Observations were carried out by a psychology graduate therapist across sixteen sessions in total. Data were analyzed using graphic analysis by comparing concentration duration in each session and calculating the average scores for Baseline 1, Intervention, and Baseline 2. The results showed that the collage game intervention had a positive effect on increasing concentration duration in children with intellectual developmental disorders. This is demonstrated by the scores obtained: Baseline 1 (24), Intervention (17), and Baseline 2 (25). There was a noticeable increase from Baseline 1 to Baseline 2. Thus, collage games are effective for improving children’s concentration during learning activities.